Studi Kondisi Lingkungan Rumah dan Perilaku Masyarakat Sebagai Faktor Risiko Kejadian Filariasis di Kecamatan Buaran dan Tirto Kabupaten Pekalongan - Yudi Syuhada; Nurjazuli Nurjazuli; Nur Endah Wahyuningsih (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2012)
Background: Filariasis is contagious disease that caused by microfilaria and fillaria parasite and it transmitted by mosquito bite. Indonesia is endemic fillariasis with high cases of Filariasis (Mf rate) 3,2%. Buaran and Tirto district In 2010, is endemic filariasis area, with microfilariasis cases as 1,9% and 2,3%. The microfilaria will infected the limfatic and evoke filariasis limfatic. Aim: To describe and to find out the relationships between: environmental and behaviour risk with the filariasis cases. Methode: This research used case control design with 52 cases and control. Risk factor that include is crowded house, existence of disch, water plant, marsh, rice field, dampoess, gaste at ventilation, livestock in a home, habit to use certain, to use use remedy agains grists, to stay out of the house in the night. Analisis mothede with univariat, bivariat and multivariate technique. Result: The result of the research showed that crowded house (OR=3,364), existence of gauze at ventilation (OR=3,600), existence livestock in home (OR=2,644), habit using mosquito spraying/coil (OR=2,956), habit of staying outside the house in the night (OR=3,576), is meaningful be fillariasis infection. The result of multivariate analysis found that the most potent variable that influent filariasis was existence crowded house, existence of gaste at ventilation, existence livestock in a home, habit of using anti mosquito drug , habit to stay out of the house in the night. Conclusion: That crowded house, existence of gaste at ventilation, existence livestock in a home, habit to use remedy agains grists, habit to stay out of the house in the night is risk factor that the most dominant for fillariasis infection. Key Words : environmental, behavioral, fillariasis, Pekalongan regency